Three new species and a new record of Anacaena Thomson, 1859 from China, with taxonomic revision to two species (Coleoptera: Hydrophilidae: Chaetarthriinae) - Jia, Feng-Long; Mai, Zu-Qi (Zootaxa, 2026)
Three new species of Anacaena Thomson, 1859 from China are described: Anacaena rinqenbungsiana sp. nov. (Xizang), A. robertangusi sp. nov. (Sichuan) and A. zhangdandanae sp. nov. (Guangxi). Anacaena jaegeri Komarek, 2007 is recorded from China for the first time (Xizang). The identity of two Chinese Anacaena species are clarified: Anacaena bulbifera Pu, 1964 is synonymized with Paracymus orientalis Orchymont, 1925 and Anacaena lushanensis Pu, 1964 with Paracymus atomus Orchymont, 1925. Detailed morphological descriptions and illustrations of the new species are provided, along with an updated checklist of Anacaena species recorded from China.